The Significance of Activity in The Mental Development Of Preschool Children (Journal of Pedagogical Inventions and Practices, 2026)
This article examines the role of activity as a decisive factor in the mental development of preschool children. Early childhood is a sensitive period in which cognitive processes, speech, imagination, memory, attention, and elementary forms of reasoning develop intensively. In this stage, the child does not acquire knowledge passively; rather, mental growth occurs through purposeful interaction with objects, adults, peers, symbols, and the surrounding environment. The article substantiates the idea that activitybased experience serves as the psychological foundation of intellectual maturation in preschool age. Particular attention is paid to play, communication, productive work, exploratory behavior, and educationally organized tasks as leading forms of activity that stimulate perception, comparison, classification, generalization, and problem-solving. The paper also analyzes the pedagogical conditions necessary for strengthening mental development in preschool education: emotionally supportive communication, a rich developmental environment, age-appropriate tasks, integration of speech and action, and the active participation of adults in guiding children’s independent efforts. It is argued that activity is not merely a background condition of development, but the core mechanism through which the child transforms external experience into internal mental structures. The article concludes that the effectiveness of preschool education depends largely on how consistently children are involved in meaningful, diverse, and developmentally appropriate activities.